Deleuze, axiomatized : Alain Badiou’s formalization of the upsurge. (Tábano, 2025)
This work aims to analyse Alain Badiou’s critique of Gilles Deleuze’s Logic of Sense and theory of the event in Logics of Worlds. This is done under the hypothesis that Badiou axiomatizes Deleuze to mathematically scrutinize the mainframe of Logic of Sense and finally break away with the empiricist approach towards the appearance of the bodies. In doing so, Badiou is able to formalize the resurgence of multiplicities per operation of the inconsistent multiple. Henceforth, this work focuses on Badiou’s employment of Deleuzian transcendentalism as an argumentative device to purport the formal condition of the appearance of bodies or multiplicities, as the vitalist analytic of the undifferentiated bodies is considered refuted.
Keywords: Badiou; Deleuze; Event; Multiplicity; Axiomatization